2020
DOI: 10.3390/atmos11111168
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the ETNA 2015 Eruption Using WRF–Chem Model and Satellite Observations

Abstract: The aim of the present work is to utilize a new functionality within the Weather Research and Forecasting model coupled with Chemistry (WRF–Chem) that allows simulating emission, transport, and settling of pollutants released during the Etna 2015 volcanic activities. This study constitutes the first systematic application of the WRF–Chem online-based approach to a specific Etna volcanic eruption, with possible effects involving the whole Mediterranean area. In this context, the attention has been focused on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…In this work and in the work by Rizza et al [32], we demonstrated that the model WRF-Chem may be utilized for forecast simulations of meteorology and ash/gas dispersion of Mount Etna emissions. In addition, it may also be particularly useful to better understand its impact on the meteorological phenomena over the whole Mediterranean area.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In this work and in the work by Rizza et al [32], we demonstrated that the model WRF-Chem may be utilized for forecast simulations of meteorology and ash/gas dispersion of Mount Etna emissions. In addition, it may also be particularly useful to better understand its impact on the meteorological phenomena over the whole Mediterranean area.…”
Section: Discussionmentioning
confidence: 53%
“…In this work, we investigated the effects of variable eruption source parameters on volcanic plume transport of the Mount Etna paroxysm of 23 November 2013. It represents a further application of the WRF-Chem model for Mount Etna following Rizza et al [32]. Concerning the model setup, the raw data obtained from the V2B Doppler radar system were elaborated at the WRF-Chem pre-processing level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, natural aerosol dust shows a higher concentration at 500 hPa and above in both the WC4 and WC25 simulations (Figure 6c,d). The previous study on the vertical transport of aerosols during volcanic eruption suggests that WRF-Chem simulates the process quite realistically [46,47]. Similarly, the model-based previous study demonstrates that WRF-Chem realistically simulates vertical aerosol transport during deep convection events [33].…”
Section: Aerosol Concentrationmentioning
confidence: 63%